CARA PRAKTIS MENCARI HADIS : Studi Buku Karya M. Syuhudi Ismail 1943-1995 Pakar Hadis Indonesia - budi suhartawan; Muizzatul Hasanah (DIRAYAH : Jurnal Ilmu Hadis, 2023)
This paper aims to examine/explore practical ways of searching for hadith offered by M. Syuhudi Ismail, who is known as a person who concentrates/focuses on hadith studies in the academic world. This research is a library research where in this research, the author tries his best to collect the works of M. Syuhudi Ismail, both those he wrote individually and together (anthology), tracing the works of other people who wrote about Syuhudi; and then try to analyze it thoroughly. In conducting data analysis, the writer used a qualitative descriptive analysis. From the results of this study it can be concluded that M. Syuhudi Ismail is so productive. Evidenced by the publication of his works totaling 59 pieces in the 70s to 90s. In terms of making it easier for hadith practitioners to find hadith practically, he offers two important things. Among other things: First, looking for hadith through the hadith dictionary based on the instructions for pronouncing the hadith (Takhrijul Hadith Bil Alfadz) and, Second. look for hadith through the hadith dictionary based on the topic of the problem (Takhrijul Hadith Bil-Maudhu'i).